Study on Landscape Fractal of Different Vegetation Coverage in Hilly Area of South China— Taking Conghua District of Guangzhou City as an Example - CHANG Jin; XIANG Huichang; BIAN Zhen; LIAO Jianwen (Renmin Zhujiang)
Based on the fractal theory,this paper calculates the area,fractal dimension and stability index of patches with different vegetation coverage in Conghua District,and analyzes the distribution and variation law of patch fractal characteristics in different elevation,slope and aspect.The results show that:①The vegetation condition in Conghua District is generally good,and the patch area with medium (>45%) and above vegetation coverage accounts for 86.7% of the total vegetation area.The farther it is from towns and highways,the more complex and irregular the patch shape is.② When the elevation is less than 90 m,the proportion of patch area with low,medium and low vegetation coverage is larger,and the shape of all kinds of patches is fragmented and complex.When the elevation is higher than 90 m,the fractal dimension of patches increases and the stability decreases with the increase of elevation.③The topographic slope in Conghua District is mainly below 25 degrees.The patches with low and middle vegetation coverage are mainly distributed in the area below 15 degrees,while those with high vegetation coverage are dominant in the area above 15 degrees.With the increase of slope,the fractal dimension and stability index of patches with the same vegetation coverage do not change significantly.④The vegetation condition of sunny slope is better than that of shady slope,but the patch structure of shady slope is more complex.